Performan Anak Babi Silangan Berdasarkan Paritas Induknya - N Wahyuningsih; Y B P. Subagyo; Sunarto Sunarto; Sigit Prastowo; N Widyas (Universitas Sebelas Maret (UNS), 2012)
The aim of this study was to determine the effect of performance of the parent parity of hybrid piglets, and to know the parity that produces good performance of the hybrid piglets. This research was conducted for four months in the company of CV. Adhi Farm in Kebakkramat, Karanganyar. The material were three boars (Landrace, Duroc and Hampshire), 21 Landrace sows, piglets from the marriage, and the data from the company. The design of experiments was nested design. The variables that were observed or estimated included birth weight, littersize, the correlation of littersize to the birth weight, and birth weight variation in birth. The data showed the influence, then followed by Least Significant Difference Test (Least Significant Difference) for parity nested in males and Duncan's Multiple Range Test for parity. The results showed that parity and male parity nested exerted a highly significant (P <0.01) for birth weight and littersize. Between birth weight and littersize were compared from each parity and each male parity nested were significantly different (P<0.05). Balanced birth weight and hybrid piglets littersize were at parity 1. The correlation between weight birth and littersize were -0,17. The variation in birth weight per littersize was 0,02 to 0,16. The conclusion of this study is the influence of the parity sow has effect on birth weight of piglet’s performance of hybrids and littersize.Keywords: performance, piglets, sow parity